Checking and washing rituals are reflected in altered cortical thickness in obsessive-compulsive disorder. (August 2019) - Wagner, Gerd; Köhler, Stefanie; Peikert, Gregor; de la Cruz, Feliberto; Reess, Tim Jonas; Rus, Oana Georgiana; Schultz, C. Christoph; Koch, Kathrin; Bär, Karl-Jürgen
Abstract: There is growing evidence for structural brain alterations in obsessive-compulsive disorder (OCD). The overall picture is however rather heterogeneous. To detect meaningful associations between clinical symptom profiles and structural alterations, we applied a classification approach, the k-means cluster analysis on clinical data, i.e., the Obsessive Compulsive Inventory-Revised (OCI-R) questionnaire. 73 OCD patients were assigned to three distinct symptom profiles. Using structural MRI and surface-based morphometric analysis (SBM), we compared cortical thickness between all OCD patients and 69 matched healthy subjects as well as among patients according to three symptom profiles. The total sample of OCD patients exhibited a thicker cortex in the pre-supplementary motor cortex (pre-SMA), dorsomedial prefrontal (DMPFC), anterior cingulate cortex and in the right anterior insula. Comparing patients of the three symptom clusters, a subgroup of OCD patients with a specific symptom profile was identified, which showed a thicker cortex in pre-SMA/DMPFC and in the contralateral primary motor cortex. In contrast to both other subgroups, patients in this group were mainly characterized by the predominance of a combination of checking and washing rituals. The other two OCD symptom subgroups showed comparable cortical thickness to healthy controls. Higher cortical thickness in regions of the motor circuitry seems to be related to motor activity-induced neuroplasticity in a specific group of OCD patients. Thicker anterior insular cortex in the total sample of patients points toward a more general pathophysiological process in OCD and potentially indicates abnormal interoceptive processing in OCD.